Investigation of Sports-Trained Students' Eating Habits according to Some Parameters Before and During the Coronavirus Outbreak - Yildirim, Yunus; Muftuoglu, Necla Ezgi; Imamoglu, Osman (Progress in Nutrition, 2021)
Study Objectives: The aim of this study was to investigate the eating habits of university sports trained students according to some parameters during the coronavirus pandemic. Methods: The questionnaires filled out by a total of 333 students studying at Mersin University Faculty of Sport Sciences were evaluated. Independent t-test, paired t-test, one-way variance analysis, and LSD tests were used in statistical processes (p>0.05). Results: Students' pre-pandemic eating habits scores are significantly lower than those of the pandemic eating habits (p